2008
DOI: 10.1163/156916208x311638
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Higher Education in First-Generation Hispanic College Students Enrolled in an Academic Support Program: A Phenomenological Analysis

Abstract: Numerous empirical studies have been conducted to examine first-generation college students, those individuals whose parents have not attended college. Their personality characteristics, cognitive development, academic preparation, and first-year performance have all been topics of research; yet there appears to be little in the literature exploring the motivation of these individuals to seek higher education. There are even fewer studies targeting academic motivation in Hispanic students. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…These students tend to have lower educational aspiration than students whose parents attended college [23]. Furthermore, parents who did not attend college tend to have less direct knowledge of the economic and social benefits of earning a postsecondary degree.…”
Section: Familial Expectations and Support Of First-generation Latino Cmentioning
confidence: 98%
See 1 more Smart Citation
“…These students tend to have lower educational aspiration than students whose parents attended college [23]. Furthermore, parents who did not attend college tend to have less direct knowledge of the economic and social benefits of earning a postsecondary degree.…”
Section: Familial Expectations and Support Of First-generation Latino Cmentioning
confidence: 98%
“…A substantial amount of research indicates that first-generation students perceive a lower level of family support and less knowledge of the college environment from their parents [22,23,27]. This is important to consider since other research has suggested that parental encouragement, involvement and overall support are some of the most significant predictors of postsecondary educational aspirations [28].…”
Section: Familial Expectations and Support Of First-generation Latino Cmentioning
confidence: 99%
“…Sosa (2002) noted that since 90% of Hispanics do not have a familial tradition for higher education, this may produce a lack of family commitment to enrollment as well as a suspicion that the liberal college culture may negatively influence their children's values. The decision to pursue higher education for some first-generation Hispanic students may require a purposeful break in regard to familial and socio-cultural traditions (Olive, 2008). For these students, collectivist and individualistic values and traditional and modern contexts may conflict within the higher education environment (Chavez & Rudolph, 2007).…”
Section: First-generation and Hispanic Studentsmentioning
confidence: 99%
“…Although the number of first-generation Hispanic college students is increasing (Saenz, Hurtado, Barrera, Wolf, & Yeung, 2007), Hispanic students earned only 5.9% of the total 625,023 master's degrees awarded in the United States in academic year -2008(u.s. Department of Education, 2010. This number represents an increase of 2% over a ten year period; however, the United Census Bureau (2011) reports between years 2000 and 2010, the Hispanic population grew by 43%, or four times the nation's 9.7% growth rate.…”
mentioning
confidence: 99%
“…When recruiting this demographic, Fischer [1] indicates that there are transition needs specific to Hispanic students. It is important to recognize the cultural factors involved with being disconnected from their families not only by distance but by the mere desire to pursue a college degree [2]. Even when their desire is great, there is an intense intergroup anxiety [3] about interaction with the new community found on the college campus.…”
Section: Literature Reviewmentioning
confidence: 99%